1983
DOI: 10.1002/1097-0142(19830315)51:6<1091::aid-cncr2820510620>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Glucagonomas: Ultrastructure and immunocytochemistry

Abstract: Pancreatic tumors harboring glucagon immunoreactive cells were found in four patients with diabetes mellitus. Alpha‐cell (glucagon) granules were present in three tumors; pancreatic polypeptide (PP) immunoreactive cells were detected in two. In two patients the tumors were malignant and one of these had the glucagonoma syndrome; the other was a member of a family with MEN‐type I syndrome. These cases illustrate three clinical subtypes of glucagonoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…At present, there is no plausible explanation for the association between pancreatic polypeptide expression and VEGF-C expression, apart from the observation that glucagonomas frequently co-express pancreatic polypeptide. 35 Although there is ample experimental evidence of an association between VEGF-C expression and lymphangiogenesis, 36 -40 this relationship is less conspicuous in human tumors. A correlation between VEGF-C expression and high LVD was recently reported in a small series of oral squamous cell carcinomas 41 but has been shown to be absent in melanomas 3,4 and in squamous cell carcinomas of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there is no plausible explanation for the association between pancreatic polypeptide expression and VEGF-C expression, apart from the observation that glucagonomas frequently co-express pancreatic polypeptide. 35 Although there is ample experimental evidence of an association between VEGF-C expression and lymphangiogenesis, 36 -40 this relationship is less conspicuous in human tumors. A correlation between VEGF-C expression and high LVD was recently reported in a small series of oral squamous cell carcinomas 41 but has been shown to be absent in melanomas 3,4 and in squamous cell carcinomas of the head and neck.…”
Section: Discussionmentioning
confidence: 99%
“…Although the secretory response of plasma glucagon has been investigated in patients with suspected glucagonoma, the diagnostic value of provocation tests has been inconclusive (Stacpoole et al, 1981a;1981b;Fujita et al, 1986). Although pancreatic islet tumours constitute an integral component of the multiple endocrine neoplasia type 1 (MEN 1), the association of glucagonoma syndrome in MEN 1 is rare (Warner et al, 1983;Stacpoole et al, 1981a;Klöppel & Heitz, 1988). Skogseid et al (1987) reported that MEN 1 patients with even no pancreatic endocrine tumours had significantly higher mean basal levels of plasma glucagon.…”
Section: Discussionmentioning
confidence: 99%
“…31 The gastrinomas in these patients reside predominantly in the proximal part of the duodenum, are usually smaller than 1 cm in diameter, and show multicentricity (see section on gastrinomas above). The occurrence of WDHA syndrome, 2,147 glucagonoma syndrome, 179,180 or acromegaly due to a tumor-secreting growth-hormone-releasing factor 156,157 is very rare in the setting of MEN1.…”
Section: Pancreatic Endocrine Tumors In Multiple Endocrine Syndrome Tmentioning
confidence: 99%